Associations between pre-surgical daily opioid use and short-term outcomes following knee or hip arthroplasty: a prospective, exploratory cohort study - Justine M. Naylor; Natalie Pavlovic; Melissa Farrugia; Shaniya Ogul; Danella Hackett; Anthony Wan; Sam Adie; Bernadette Brady; Leeanne Gray; Rachael Wright; Michelle Nazar; Wei Xuan (BMC Musculoskeletal Disorders, 2020)
Abstract Background Retrospective studies have found that daily opioid use pre-arthroplasty predicts worse longer-term service, clinical and patient-reported outcomes. Prospective studies are needed to confirm these observations. This prospective, exploratory study aimed to determine: the proportion of total knee or hip arthroplasty (TKA, THA) patients who use opioids regularly (daily) pre-surgery; if opioid use pre-surgery is associated with acute and sub-acute outcomes to 12-weeks post-surgery. Methods Consecutive patients undergoing primary TKA or THA were prospectively enrolled pre-surgery and followed-up by telephone to 12-weeks post-surgery. Acute-care (oral morphine equivalent dosage (OMED), length of stay, discharge to inpatient rehabilitation, complications) and 12-week outcomes (Oxford Knee or Hip Score, Euroqol ‘today’ health score, current use of opioids, and complications including readmissions) were monitored. Unadjusted and adjusted Odds Ratios (ORs) (95% Confidence Interval, CI), Rate Ratios and β coefficients (standard error) were calculated. Results Five Hundred Twenty-One patients were included (TKA n = 381). 15.7% (95%CI 12.6 to 18.9) used opioids regularly pre-surgery. 86.8% (452/521) were available for follow-up at 12-weeks. In unadjusted analyses, pre-surgical opioid use was significantly associated with higher average acute daily OMED [β 0.40 (0.07), p <  0.001], presence of an acute complication [OR 1.75 (1.02 to 3.00)], and ongoing use of opioids at 12-weeks [OR 5.06 (2.86 to 8.93)]. After adjusting for covariates, opioid use pre-surgery remained significantly associated with average acute daily OMED [β 0.40 (0.07), p <  0.001] and ongoing use at 12-weeks [OR 5.38 (2.89 to 9.99)]. Conclusion People who take daily opioids pre-surgery have significantly greater odds for greater opioid consumption acutely and ongoing use post-surgery. Adequately powered prospective studies are required to confirm whether pre-surgical opioid use is or is not associated with poorer joint and quality of life scores or a complication in the short-term.